Reconocimiento de saberes sobre plantas medicinales como parte del área de ciencias naturales y su aplicación en la construcción de un parque botánico en la Unidad Educativa San Agustín de Cajas, con los niveles sexto y séptimo año de educación básica Cantón Otavalo. - Lechón Cabascango, Amelia (2013)
In our time at school "San Agustin de Cajas" accounts we found that children do not know about medicinal plants, but also to the teachers of the institution do not impart that knowledge in the classroom. Concerned about this situation we ask ourselves the objective: "To recognize the ancestral knowledge of medicinal plants as part of the natural sciences through research uses and medicinal properties of plants and their application in the construction of a botanical park in Unit educational "San Agustin de Cajas" canton Otavalo to socialize students, teachers and parents. "